PENERAPAN PRINSIP ERGONOMIS DALAM PROSES MENYIAPKAN TEMPAT TIDUR TAMU OLEH PARAMUGRAHA DI HOTEL CATUR ADI PUTRA DENPASAR BAL - Wayan Agung Dicki Darmawan; Ni Luh Putu Sri Widhiastuty (Universitas Triatma Mulya, 2022)
This study aims to understand the importance of applying ergonomics principles when carrying out an activity or work in the Housekeeping Department, especially when preparing guest beds by the Room boys/Room attendants. It uses a qualitative method, in which primary data will be collected through observation, documentation, and face-to-face interviews with the four informants present. Selected using purposive sampling so that they are able to understand and be aware of the case being studied and secondary data collected through documents related to the operations of the Housekeeping Department at Hotel Catur Adi Putra Denpasar. This research was initiated by identifying the problem at the object of the research, where it was seen that the Room boys/Room attendants were still bent over while making the guest bed preparation process, whether it was lifting the mattress, tidying the mattress and its mobility. Next is the making of research methods that will be used by researchers. The data sources used are primary and secondary data, while the type of data to be used is qualitative. After this research is completed, the final stage is to make a presentation of the results of the analysis, then the results will be presented in formal and informal forms.